2021
DOI: 10.1172/jci143759
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil dynamics in the tumor microenvironment

Abstract: The tumor microenvironment profoundly influences the behavior of recruited leukocytes and tissue resident immune cells. These immune cells, which inherently have environmentally-driven plasticity necessary for their roles in tissue homeostasis, dynamically interact with tumor cells and the tumor stroma and play critical roles in determining the course of disease. Among these immune cells, neutrophils were once considered much more static within the tumor microenvironment; however, some of these earlier assumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 170 publications
0
52
0
Order By: Relevance
“…According to functional differences, tumor-associated neutrophils (TANs) can be divided into two subtypes: antitumorigenic or protumorigenic neutrophils, termed N1 and N2, respectively. 173 177 TANs can be a component of tumor-promoting inflammation by promoting angiogenesis, immunosuppression, remodeling of the extracellular matrix, and metastasis. The interaction between neutrophil polarization and tumor microenvironment has been well summarized but there are few studies focusing on the relationship between TANs polarization and IR.…”
Section: Rationale Of Irtmentioning
confidence: 99%
“…According to functional differences, tumor-associated neutrophils (TANs) can be divided into two subtypes: antitumorigenic or protumorigenic neutrophils, termed N1 and N2, respectively. 173 177 TANs can be a component of tumor-promoting inflammation by promoting angiogenesis, immunosuppression, remodeling of the extracellular matrix, and metastasis. The interaction between neutrophil polarization and tumor microenvironment has been well summarized but there are few studies focusing on the relationship between TANs polarization and IR.…”
Section: Rationale Of Irtmentioning
confidence: 99%
“…Unfortunately, PLR, MLR and SII were not associated with the response to the anti-PD-1 treatment in ESCC patients, as a result of which, it was assuming that NLR was a vital factor reflecting the system inflammation response after anti-PD-1 therapy. Neutrophil and lymphocyte were important components of tumor immune microenvironment and played a role in tumor-associated immunity [ 36 38 ], but the mechanism of the significance of peripheral blood NLR which representing systemic inflammation in tumor-associated immunity was still unclear. In our study, we also evaluated the NLR level of the tumor free population and found that the NLR level of ESCC patients had a significantly higher trend than that of the tumor free population.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies support the pro-tumoral properties of N2 neutrophils, that predominantly express CC and CXC chemokines such as CCL2, 3, 4, 8, 12, and 17 and CXCL1, 2, 8, and 16, in addition to higher expression of vascular endothelial growth factor (VEGF), CXCR4 and matrix metalloproteinase 9 (MMP9) [14][15][16] (Figure 1B). Molecularly, one of the first mechanisms through which neutrophils promote tumor growth is represented by the release of ROS, which in turn induce DNA damage, which are essential for cancer initiation, cell proliferation, and increasing the mutational load [14][15][16].…”
Section: Introduction 1brief Overview On Neutrophils and Cancersmentioning
confidence: 67%